A systematic review of studies on ethnic minority youth development in Hong Kong: an application of the ecological framework. Issue 3 (1st September 2016) - Arat, Gizem; Hoang, Andrew P.; Jordan, Lucy P.; Wong, Paul W. C.
Abstract: Ethnic minority young people play a significant role in the socio-economic growth of an ageing society with a decreasing fertility rate. The successful social integration of individuals with diverse cultural backgrounds within a society is a core value of the social work profession. This study examines the understanding of ethnic minority youth development in Hong Kong using a systematic review methodology. Risk prevention and positive promotion factors were identified using Bronfenbrenner's ecological framework. Articles were searched through multiple databases in English, and 36 academic articles were reviewed. These studies mainly examined the risks of academic failure of these students in Hong Kong while few focused on the positive directions of multidimensional youth development. Future social work research and practice should examine positive youth development for ethnic minorities which can inform social work practice in Hong Kong and within other East Asian traditionally ethnically homogeneous societies undergoing significant changes in ethnic diversity.